Green building in developing countries : policy, strategy and technology - Gou, Zhonghua (Cham, Switzerland : Springer, 2020)
The book reveals how green buildings are currently being adapted and applied in developing countries. It includes the major developing countries such as China, Indonesia, Malaysia, Thailand, Pakistan, Cambodia, Ghana, Nigeria and countries from the Middle East and gathers the insights of respected green building researchers from these areas to map out the developing worlds green building revolution. The book highlights these countries contribution to tackling climate change, emphasising the green building benefits and the research behind them. The contributing authors explore how the green building revolution has spread to developing countries and how national governments have initiated their own green building policies and agendas. They also explore how the market has echoed the green building policy, and how a business case for green buildings has been established. In turn, they show how an international set of green building standards, in the form of various techniques and tools, has been incorporated into local building and construction practices. In closing, they demonstrate how the developing world is emerging as a key player for addressing the energy and environmental problems currently facing the world. The book helps developers, designers and policy- makers in governments and green building stakeholders to make better decisions on the basis of global and local conditions. It is also of interest to engineers, designers, facility managers and researchers, as it provides a holistic picture of how the industry is responding to the worldwide call for greener and more sustainable buildings
Keywords: Sustainable construction -- Developing countries; Sustainable buildings -- Developing countries; Green movement -- Developing countries